Feasibility, acceptability and preliminary effects of a social network-based, peer-led HIV self-testing intervention among men in two Ugandan fishing communities, 2022 - Joseph KB Matovu; Aisha Twahiri Namwama; Linda Kemigisha; Geoffrey Taasi; Jennipher Nakabugo; Julius Wandabwa; Laura M. Bogart; Nuraan Fakier; Rhoda K. Wanyenze; Peter Olupot-Olupot; Joshua Musinguzi; David Serwadda (Archives of Public Health)
Abstract Background Social network-based interventions can improve uptake of health interventions. However, limited evidence exists on their feasibility and acceptability in fishing community settings. We assessed the feasibility, acceptability and preliminary effects of a social network-based, peer-led HIV self-testing (HIVST) intervention among men in Uganda. Methods The PEer-led HIVST intervention for MEN (PEST4MEN) is a pilot intervention conducted among men in Kalangala and Buvuma districts. Baseline data were collected in July 2022 and follow-up data in September 2022. The intervention was implemented through 22 trained lay men (“peer-leaders”) who received training in HIVST use and distribution processes and requested to refer at least 20 male members from their social networks for study eligibility screening. To be eligible, men had to be aged 15 years or older with unknown or HIV-negative status. After the baseline interview, men were requested to pick two oral fluid-based HIVST kits from their peer-leaders. The intervention was deemed feasible if peer-leaders gave-out > 80% of the kits and acceptable if > 80% of the kits’ recipients used them to self-test for HIV. At the follow-up interview, newly diagnosed HIV-positive men were asked if they had linked to HIV care. Data were descriptively analyzed using STATA version 16.0. Results Of 475 screened men, 400 (84.2%) met the eligibility criteria and completed the baseline interview. Of these, 56.7% (n = 227) were engaged in fishing or fishing-related activities. At follow-up, 361 men (90.2%) were interviewed; 98.3% (n = 355) received at least one kit from their peer-leaders. Nearly all (99.1%, n = 352) kits’ recipients used them to self-test for HIV. Of the 352 HIV self-testers, 51 men (14.5%) had reactive (positive) HIV self-test results. Nearly one-third of the HIV self-tested men (31.4%, n = 16) were first-time HIV-positive testers. Of these, 87.5% (n = 14) went for confirmatory HIV testing, 50.0% (n = 7) were confirmed as HIV-positive and 71.4% (n = 5) were linked to HIV care. Conclusion Our peer-led HIVST intervention was feasible and acceptable and identified newly diagnosed HIV-positive men who were linked to HIV care. However, while these results are promising, we recommend additional research in a randomized controlled trial prior to the eventual roll-out of this intervention. Trial registration ClinicalTrials.Gov: NCT05685498 (retrospectively registered on January 17, 2023).